STUDI TENTANG EMOSI PSIKOLOGIS DALAM MENINGKATKAN INTENSITAS PEMBELIAN IMPULSIF D’COSMO SEMARANG - Hidayat, Eka Novian (Master of Management Diponegoro University, 2015)
The purpose of this research was to test the influences of acces easyless, and persuasivecommunication toward psychology emotions to increase impulsive purchasing intentions. The usage of these variables was able to solve the arising problem within D’Cosmo Semarang. The problem in this research was the decreasing of sales. It needed more attention bea•ause the consumer feel about the D’Cosmo Semarang could affecting impulsive purchase intentions.The samples of this research consisted of a hundred customer’s on D’Cosmo Samarang. The analysis technique used here is multiple regression with the least square difference and hypothesis tast using -statistic to examine partial regression coefficient and I-statistic to examine the mean of mutual effect with level of significance 5°/o. In addition, classical assumption was a/so performed including normality test, multicolinearity test, and heteroscedasticity test.The result of ltte analysis showed that acces easyless, and persuasive communication contributes an positive influence, which is significant to pcyshology emmotions to increase impulsive purchase intentions. The empirical result indicated that to increase impulsive purchase intentions of D’Cosmo Semarang, management need to pay attention on factors like acces easy/ess, and persuasive communication, because that is the factors that effect high or low level of impulsive purchase intentions..